THE INFLUENCE OF EMOTIONAL BRANDING TO CUSTOMER LOYALTY: A QUALITATIVE ASSESSMENT - Dinda Fresiana, Anisa
Nowadays, Businesses or brands collaborate with their customers to fulfill their desires and aspirations. The cosmetic industry in Indonesia is competing to create a product and service which are demanded by customers. It means that the competition within cosmetic industry will continue to grow more intense. The objective of the research is to assess whether there is a relationship between four elements of emotional branding; namely Relationship, Sensorial Experience, Imagination, and Vision; to consumer loyalty. Therefore, the results of this research can be used to develop a strategy that might keep a customer loyal to a business or brand.